LINGUOPOETIC ANALYSIS OF THE IMAGE OF CHILDHOOD IN DIFFERENT SYSTEMIC LANGUAGES - TursunovaMohinur (Journal of new century innovations, 2023)
Annotation: the article tells about the linguistic analysis of the image of childhood in different systematic languages. Uzbekistan and world linguistics reflect on the assessment of linguopoetics and different approaches to this phenomenon, as well as on the scientific work done.